What do double-check routines actually detect? An observational assessment and qualitative analysis of identified inconsistencies - Yvonne Pfeiffer; Chantal Zimmermann; David L. B. Schwappach (BMJ Open)
Objectives Double checking is used in oncology to detect medication errors before administering chemotherapy. The objectives of the study were to determine the frequency of detected potential medication errors, i.e., mismatching information, and to better understand the nature of these inconsistencies.Design In observing checking procedures, field noteswere taken of all inconsistencies that nurses identified during double checking the order against the prepared chemotherapy.Setting Oncological wards and ambulatory infusion centres of three Swiss hospitals.Participants Nurses’ double checking was observed.Outcome measures In a qualitative analysis, (1) a category system for the inconsistencies was developed and (2) independently applied by two researchers.Results In 22 (3.2%) of 690 observed double checks, 28 chemotherapy-related inconsistencies were detected. Half of them related to non-matching information between order and drug label, while the other half was identified because the nurses used their own knowledge. 75% of the inconsistencies could be traced back to inappropriate orders, and the inconsistencies led to 33 subsequent or corrective actions.Conclusions In double check situations, the plausibility of the medication is often reviewed. Additionally, they serve as a correction for errors and that are made much earlier in the medication process, during order. Both results open up new opportunities for improving the medication process.